Effect of Punarnavadi Mandoora in the Management of Garbhini Pandu w.s.r to Iron Deficiency Anemia in Pregnancy –A Review - Rai, Lata; Chaturvedi, Uttara kumar (International Research Journal of Ayurveda & Yoga, 2024)
India is one of the countries where anaemia during pregnancy is common. Anemia in pregnancy is caused by a various factors. The most common disorder in a pregnant woman is iron deficiency anaemia. Rasa Pradoshaja vikara is a disorder that arises due to inappropriate Rasa Dhatu in the mother and constantly rising foetal demands. According to Ayurvedic classics, for decades, a variety of Lauha preparations have been used to treat anaemia. Punarnava Mandoora is an Ayurvedic preparation that has been described in various Ayurvedic texts. It’s a traditional Ayurvedic treatment for a variety of ailments. It works as a diuretic, cleanses the blood, and increases blood circulation. It raises hemoglobin levels and alleviates anaemia symptoms. Punarnava Mandoora is also used for Oedema, Pliha vikara (Spleen diseases), Yakruta vikara (Liver diseases), Udara (Abdominal distention), Arsha (Hemorrhoids), and Twacha vikara (Skin diseases). This review article highlightseffect of Punarnavadi mandoor in the management of Garbhini pandu W.S.R to anemia in pregnancy